Reconfigurable software-defined radar testbed with built-in validation - Juan Carlos Martínez Quintero; Edith Paola Estupiñán Cuesta; Johan Stiven García Ramírez (Bulletin of Electrical Engineering and Informatics, 2022)
This article presents a radar testbed for speed detection through micro-doppler effect in a controlled environment using software defined radio (SDR) technology. The target moves along a conveyor belt with software-controlled speed. The speed is detected by an SDR radar, and it is possible to compare it to an encoder-based sensor implemented on the testbed. The testbed as well as the SDR radar are reconfigurable and a (continuous wave) CW radar was implemented for the validation of the testbed; however, the testbed is not limited to this implementation. The testbed can be remotely operated because it includes the mechanism to move the target and control its velocity. The article shows the way in which the testbed was designed and implemented, the generation and processing of the radar signal using a limeSDR, and the validation of the radar measurements compared to the encoder-based speed sensor. The maximum speed obtained by the target in the testbed is 15.69cm/s. Results show a difference in the speed measured with the SDRadar of no more than 5% compared to the sensor measurememt. Results obtained allow characterizing the behavior of the SDR platform in the detection of low speeds.